Malaysian Muslim youth perception towards management of spirituality program in Malaysia - Elias, Nor Hanim; Maamor, Selamah; Aziz, Ahmad Bashir (Akademia Baru, 2017)
Youth development will focus on moulding a generation of youth who are educated, united, democratic, liberal and tolerant, competitive, ethical and scientifically and technologically progressive. The development of this group is crucial since they will be future leaders, professionals, technocrats, skilled and productive workforce necessary to attain developed nation status. The objectives of this paper is to measure Muslim Malaysian youth perception towards management of spirituality program. The methodology used in this research is quantitative methods to gather the primary data through questionnaire. In this study, we employed stratified sampling technique and the respondents are Muslim Malaysian youth within the age of 15 to 40 years old. The data was gathered from 3,648 respondents analysed by using descriptive analysis, t-test and Anova. From the findings, to be successful in developing Muslim youth in Malaysia, improvement need to be done on the management of spirituality activities, in term of the quality of the content and the design of the program, its implementation and the role and contribution of the knowledgeable moderator are decisive factors.